Production of protein isolate and its enzymatic hydrolysates from local pumpkin seeds and studying their functional properties - Israa O. al-karaquly; Aswan H. Bayar (مجلة مركز بحوث التقنيات الاحيائية)
Background: Pumpkin seeds are a valuable source of high-quality protein and can be utilized as functional food ingredients due to their properties, such as solubility, foam formation, and stability. This study aims to produce protein isolate and its enzymatic hydrolysates from local pumpkin seeds to study their properties. Methodology: Preparing defatted pumpkin seeds for protein extraction, followed by the enzymes’ hydrolysis using Trypsin and Pepsin enzymes separately and together in two methods. The determination of amino acids and the degree of hydrolysis was conducted; moreover, protein properties were studied, including solubility, emulsifying activity, stability index, foaming capacity, and stability.Results: A protein sample was successfully produced from local, peeled, non-soaked pumpkin seeds, yielding a protein percentage of 53.15%. Enzymatic protein hydrolysates were produced at different times. Essential and non-essential amino acids were determined. The functional properties of protein samples and protein hydrolysates were studied, including solubility at various pH levels. The higher emulsifying capacity was observed for the enzymatic hydrolysate using pepsin, while the protein sample dissolved in pH 8 had higher emulsifying stability. The enzymatic hydrolysate produced using pepsin exhibited the highest foaming capacity, while a mixed enzyme (Ma) (pepsin + trypsin) showed a higher foaming capacity and stability. Conclusion: Pumpkin seed protein has numerous nutritional values that can be utilized in the preparation of protein-rich foods for athletes and as a source of Nitrogen in microbial culturing media.